Ljubiteljska gledališča v urbanem in ruralnem okolju - Milčinski, Tara (Amfiteater (Ljubljana), 2020)
The article presents the distinction between urban and rural amateur theatres based on the ethnographic field research of two amateur theatres in Škofja Loka and Bohinjska Bela and a review of literature on the topic. The urban or rural environment does not affect amateur activity to the extent that such a distinction is necessary. The main differences are visible in the organisation of theatres and the division of tasks within them. Thus, we can divide between half-professional and amateur theatres.
Keywords: amateur theatre; audience; Gledališče Belansko; ljubiteljsko gledališče; Loški oder; publika; rural; ruralno; urban; urbano